The important thing is to lose (2003): The anti-nostalgic process and the analysis of his speech in a narrative space of the XXI century (XXI Century. Spanish Literature and Culture)
Considering the importance of nostalgia in the writing process of contemporarySpanish fiction, this article combines an analysis of the concept of counter-nostalgiawith a discourse analysis of some of the mechanisms that contribute to the narrativeconfiguration of the text. This analysis is based on the idea of agency from a syntacticperspective. To illustrate the discourse of counter-nostalgia, the authors focus on thenovel by the Spanish writer Manuel Pérez Subirana, Lo importante es perder (2003)
Keywords: agency; nostalgia; contemporary narrative; discourse analysis